Faktor-Faktor Penentu Kualitas Laporan Keuangan Pemerintah Daerah Gianyar - Rini, I Gusti Ayu Intan Saputra; Yulianti, Ni Putu Mirta (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This research aims to obtain empirical evidence regarding the influence of variables government accounting standards, accounting information systems, of internal control systems, organizational commitment, and good governance on the quality of the Gianyar Regency Regional Government's financial reports. The data in this research is primary data using questionnaire data collection techniques. This research is quantitative research with hypothesis testing. The sampling method used purposive sampling, with a sample of 100 respondents from a population of 25 OPDs (Regional Apparatus Organizations) in Gianyar Regency. Based on the results of data processing using multiple linear regression analysis techniques, it is proven that the variables of government accounting standards, accounting information systems, internal control systems, organizational commitment, and good governance, have a positive effect on the quality of the Gianyar Regional Government's financial reports.